Spatial modelling of the temperature at the top of Permafrost in Cierva Point (Antarctic Peninsula) - Ramos Marín, Sara (2019)
The Western Antarctic Peninsula (WAP) has shown complex reactions to climate change in the last decades. To evaluate the changes occurring in these environments, permafrost and active layer monitoring and modelling are essential. In this dissertation, the characteristics of the ground temperature regime are analysed and the spatial distribution of the “Temperature at the Top of Permafrost” (TTOP) in Cierva Point (Danco Coast, WAP) is estimated using topo-climatic information over an area of 0.65 km2. With the results, the climate sensitivity of permafrost in this area and the potential impact of small climate change in its extent are evaluated. A first evaluation of the temperature regimes allowed to determine the temperature and depth of the permafrost table and the ground thermal offset using observed borehole and climate data from nine different monitoring sites, in selected periods from 2012 to 2018. The top of permafrost was observed at depths of 0.4, 1 and 5m and the temperature at these depths was observed to be -1.4 ºC, -2.6 ºC and 1.2 ºC in these locations. For the monitoring boreholes where the top of permafrost was not reached, the depth of the top of permafrost was estimated to range between 0.4 and 5 m with temperatures ranging between -0.2 ºC and -2.6 ºC. The results were used together with topographic data to implement the spatial TTOP model using a Geographical Information System (GIS)-based methodology to implement a high-resolution model (1 x 1 m grid cell) that allows a further insight into the spatial characteristics of permafrost. Permafrost was estimated to be present in nearly 88% of the area and the lower TTOP values were found at high altitudes and unconsolidated soil or peat areas covered by moss. The highest TTOP results were found at low altitudes, bare surfaces and concave areas. Bare surfaces increase exposure to solar radiation during the summer and the concavity of the terrain promotes higher snowpack accumulation during the winter, which acts as a good thermal insulator hindering ground energy loses. In the areas where the mean temperature at the top of permafrost was found to be higher than 0 ºC, permafrost is absent and the TTOP stands for the temperature at the base of the seasonal freezing layer. An increment of the TTOP was observed in case of a hypothetical long-term increase of 1 ºC in the MAAT and the results suggest the disappearance of nearly 50% of the current modelled permafrost area. Ground temperatures resulted to be more sensitive to the temperature increment at bare ground surfaces and/or concave sites. The less sensitive areas were the ones covered by moss formations as well as the most convex. Permafrost degradation in Cierva Point, which is an Antarctic Specially Protected Area, may lead to significate impacts in the local ecosystem.